The Instruments of Boosting Innovation Processes - Pawlik, Andrzej (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Innovation is considered to be a need of the knowledge-based economy nowadays. In the meantime, its level regarding to the Polish economy, provinces and society is far from the one that is expected. Existing definitions in the literature explain innovation as the ability to explore and create new solutions, adapt them to specific conditions, implement in practice, and then apply in the wider field. Innovation means also the capacity to create, implement and promote innovation. As a result of the innovativeness the new grounds for improving the quality of life, social welfare are created. What is more, the innovativeness builds up a favourable conditions for the improvement of living conditions in the cities. The aim of this essay is to present the institutions which contribute to innovativeness of the cities and regions through boosting the innovation processes. It is important to focus on the role of the technology parks and technology transfer centers in the process because the growth of innovation will not happen overnight.